On Program Synthesis and Large Language Models. - Hüttel, Hans (Communications of the ACM, 2025)
An opinion is presented in which the author argues that computer programming is unlikely to become obsolete due to artificial intelligence. Topics of discussion include computational complexity theory, the use of English as a programming language, the generation of correct program code, and the problem of program synthesis.